(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This research focuses on the comparative analysis of national-cultural semantically marked lexical units in structurally different languages, primarily Uzbek and English. The study aims to investigate how language serves as a cultural mirror, encoding specific values, traditions, and social perceptions through semantically rich vocabulary. Through a linguistic and cultural lens, the paper examines how these lexical units embody national identity and reflect a community’s worldview. Special attention is given to difficulties encountered in the translation of such culturally loaded terms due to the absence of direct equivalents across languages. The research highlights the importance of understanding semantic nuances to ensure effective cross-cultural communication and accurate translation. The findings of this study contribute to a deeper appreciation of the interaction between language, culture, and meaning.